PENGARUH PENGEMBALIAN ASET DAN RASIO UTANG ATAS EKUITAS TERHADAP NILAI PERUSAHAAN PT BANK CENTRAL ASIA TBK - Ruth Theresia Situmorang; M. Kausar Maulana (Jurnal Ekonomi dan Industri, 2025)
The purpose of this study is to analyze the effect of return on asset and debt to equity ratio on enterprise value at PT Bank Central Asia Tbk. This research was conducted at companies engaged in the banking sector, namely PT. Bank Central Asia Tbk. The data used in this study is secondary data consisting of quarterly financial reports.The analytical method uses multiple linear regression analysis. The results of the study are as follows: 1) Return on asset and debt equity ratio together have a significant effect on enterprise value at PT. Bank Central Asia Tbk. 2) Return on asset has an effect not significant on enterprise value .3) Debt to equity has a positive and significant effect on enterprise value.